Index of Real Sector Returns as Price Benchmarking for Islamic Banking Products - Researchers of Islamic Banking Department (Institute for Research and Community Empowerment (LPPM TAZKIA), 2012)
Objective – Islamic Banking is closely related to the real sector. Then, its operation should reflect the real sector which is expected to contribute to the sustainable economic growth. Nevertheless, Islamic banks are still benchmarking the price of their products (profit sharing and sales) on interest rate. This is as an implication of the implementation of the dual banking system. Moreover, the small portion of Islamic banking compared to the total national banks causes the competitiveness of Islamic banking product in terms of pricing has a high correlation with the interest rate of conventional counterpart. This phenomenon indicates the need to find.Method – This research employed library research method since this paper relies on secondary data by thoroughly reviewing the most relevant literature. The paper attempt to propose a pricing indicator which is based on the real sector activities as the root of Islamic banking operations.Result – Theoretically, this indicator can reflect the real rate of return of every industry sector. In addition, it can help Bank Indonesia to monitor the real sector performance and analyze the possible gap between real sector activities and financial sector. Furthermore, when the benchmark of real rate of real sector return is available, the return index of Islamic banking reflecting the profit sharing performance of the whole Islamic banking industry can be formulated. This concept is different with other indexes which are corresponding to the price of financial assets.Conclusion – In general, return index of real sector as a reference for Islamic banking product pricing is expected to define the way of non-interest return analysis, to calculate the non-interest return of selected sectors that becomes the focus of analysis using Cash Recovery Rates (CRR), forming an index of industry by sector in the second stage, by doing a certain weighting of those companies, to analyze the relationship between macro factors and CRR by sector and to forecast.